1997
DOI: 10.1152/jappl.1997.83.3.867
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of human skeletal muscle in vivo: comparison of isometric, concentric, and eccentric muscle action

Abstract: The purpose of this study was to estimate the efficiency of ATP utilization for concentric, eccentric, and isometric muscle action in the human tibialis anterior and extensor digitorum longus in vivo. A dynamometer was used to quantitate muscle work, or tension, while simultaneous 31P-nuclear magnetic resonance data were collected to monitor ATP, phosphocreatine, inorganic phosphate, and pH. The relative efficiency of the actions was estimated in two ways: steady-state effects on high-energy phosphates and a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
142
2
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(161 citation statements)
references
References 41 publications
10
142
2
3
Order By: Relevance
“…When comparing the FR to SIX methods it was found that blood lactate response were not different between them, despite executing 77% more repetitions and work (p < 0.01) and been submitted to 52,14% more TUT (p < 0.01) during the FR method. The fact that the FR method did not produce superior lactate responses when compared to SIX is in agreement with previous findings (17) and it is not unexpected, since eccentric contractions have been shown to induce a decreased metabolic stress (19,(27)(28)(29) . The rationale for using the FR method probably lies in the neuromuscular characteristics of eccentric actions.…”
Section: Discussionsupporting
confidence: 92%
“…When comparing the FR to SIX methods it was found that blood lactate response were not different between them, despite executing 77% more repetitions and work (p < 0.01) and been submitted to 52,14% more TUT (p < 0.01) during the FR method. The fact that the FR method did not produce superior lactate responses when compared to SIX is in agreement with previous findings (17) and it is not unexpected, since eccentric contractions have been shown to induce a decreased metabolic stress (19,(27)(28)(29) . The rationale for using the FR method probably lies in the neuromuscular characteristics of eccentric actions.…”
Section: Discussionsupporting
confidence: 92%
“…We acknowledge that there are also metabolic costs associated with muscle activation, isometric muscle force production and negative muscle work (Beltman et al, 2004;Hogan et al, 1998;Ryschon et al, 1997), but evidence suggests that metabolic energy expenditure during walking is dominated by the cost of performing positive muscle work. Recent studies indicate that muscles perform substantially more positive work than negative work during level walking (DeVita et al, 2007;Umberger and Martin, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with two recent studies of active Y individuals, which found higher oxidative capacity in the MG than in the TA (Forbes et al 2009b;Gregory et al 2001), despite the higher percentage of type I fibers in the TA. The authors of both previous studies reasoned that the athletic events the active subjects participated in likely involved frequent concentric contractions of the gastrocnemius (Gottschall and Kram 2003), which are more energetically costly than the largely eccentric contractions of the TA (Ryschon et al 1997). Regular participation in these activities may be a strong stimulus for increasing oxidative capacity in the MG. By contrast, the largely eccentric action of the TA during these activities may be a less potent stimulus for adaptation, leading to comparatively modest increases in the TA.…”
Section: Muscle Differencesmentioning
confidence: 99%